The Nordic Football Injury Audit: higher injury rates for professional football clubs with third-generation artificial turf at their home venue - Kristenson, K.; Bjørneboe, J.; Walden, M.; Andersen, T. E.; Ekstrand, J.; Hägglund, M. (British Journal of Sports Medicine, 2013)
Background: Previously, no difference in acute injury rate has been found when playing football on artificial turf (AT) compared with natural grass (NG).